EFFECT OF NURSE CARING BEHAVIOR AND COMMUNICATION ON INPATIENTS SATISFACTION - Liza Afriliana; Chriswardani Suryawati; Luky Dwiantoro (International Journal of Artificial Intelligence Research, 2022)
Background: Patient satisfaction is very important in health services in hospitals. A decrease in patient satisfaction will have an impact on a decrease in the number of patients in the hospital. Caring and communication behavior are examples of attitudes that must be considered in nursing care for patients.Purpose: This study aimed to evaluate the effect of caring behavior and nurse communication on inpatient satisfaction.Methods: This cross-sectional study involved 125 inpatients at Puri Asih Hospital Salatiga, Indonesia. Patients who fit the inclusion and exclusion criteria were taken by purposive sampling method. The caring behavior questionnaire used the Caring Dimension Inventory (CDI) instrument, nurse communication was assessed by the Nurse Quality of Communication with Patient Questionnaire (NQCPQ), and patient satisfaction by the La Monica Oberst patient satisfaction scale (LOPSS) in the Indonesian version. The Chi-square test and logistic regression were used in this study.Results: Caring behavior and nurse communication significantly affect patient satisfaction (p < 0.001). Caring behavior and good nurse communication can protect against low patient satisfaction by 69% each (OR = 0.31, 95% CI: 0.134-0.721).Conclusion: Good caring behavior and communication can prevent patient dissatisfaction. Caring behavior and nurse communication must be continuously improved to increase patient satisfaction.